„[Z]a wcześnie dos„[Z]a wcześnie doszliśmy/ do brzegów poznania” – językowa kreacja drogi w tomiku Po obu stronach słowa Oleny Duć-Fajferzliśmy/ do brzegów poznania” – językowa kreacja drogi w tomiku Po obu stronach słowa Oleny Duć-Fajfer - Rychter, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The image of the road and wandering is a recurring theme in the poems collected in the volume Po obu stronach słowa [On both sides of the word] by Olena Duć-Fajfer. Road is a symbolic and ambiguous component of space experienced by the Lemko people, which is depicted by the use of the noun droga [road] and its synonyms ścieżka [path] and labirynt [maze] as well as adverbs blisko [near] and daleko [far], and pronouns tam [there]. The author uses a number of verbal forms (verbs and participles). As regards the cultural experience of space, one may say that Olena Duć-Fajfer considers Lemkivshchyna to be the centre of the world, a sacred place. For her, each Lemko is on its periphery, in the profane, and spends his or her life trying to reach the centre. The Lemkos can be compared to the pilgrims of the Romantic era, as they searched for their nineteenth-century homeland while in exile; they missed their homeland in terms of both geography (space) and spirituality (culture and symbolism).